Spatial Modulation of linear and quadratic susceptibilities in Lithium Niobate crystals by using femtosecond laser pulses - Torchia, Gustavo Adrián (2006)
In this work we present the spatial control of the linear susceptibility (χ1) in Lithium Niobate crystals by means of infrared (800 nm) femtosecond interaction. Diffraction gratings have been performed on the surface (relief) and inside (phase) of these samples by femtosecond laser writing. Also we have performed a spatial control of the quadratic susceptibility (χ 2 ) by direct writing of a pattern of ferroelectric domains on the surface of z cut substrates by using the second harmonic femtosecond pulses (400 nm). Finally, efficient photonic devices for second harmonic generation via quasi phase matching could be obtained following the experimental procedure presented in this work.